Protein and mineral content in sorghum silage with grasses and urea - Cruz, S. S.; Pascoaloto, I. M. [UNESP]; Andreotti, M. [UNESP]; Lima, G. C. [UNESP]; Lattari, J. V.F. [UNESP]; Soares, D. A. [UNESP]; Morais, G. N. [UNESP]; Dickmann, L. [UNESP] (My University, 2019)
Knowing cultivation dynamics of sorghum intercropped with tropical forage for silage production is important both for animal nutrition and for the quality of the food, as well as for the sustainability of the agricultural production system. Following this logic, the objective of this research was to evaluate the gross protein and macronutrient contents of sorghum silages in consortium with marandu grass or mombaça grass with increasing doses of urea. The experimental design was a 3 x 5 factorial randomized block design with three types of silage (forage sorghum in monoculture and forage sorghum in consortium with Urochloa brizantha cv. Marandu or with Megathyrsus maximus cv. Mombaça) and five urea doses as silage additive (0, 2.5, 5.0 and 7.5%). The levels of crude protein and macronutrients (P, K, Ca, Mg and S) were determined before and after the ensiling process. The higher the urea dose used the higher the crude protein content. The addition of urea may result in lower Ca and S losses and higher Mg losses during the ensiling process.
Teor proteico e mineral das silagens de sorgo consorciadas com gramíneas aditivadas com ureia
Keywords: Consortium; Megathyrsus maximus; Urochloa brizantha